Potential benefits of music playing in stroke upper limb motor rehabilitation. (May 2020) - Grau-Sánchez, Jennifer; Münte, Thomas F.; Altenmüller, Eckart; Duarte, Esther; Rodríguez-Fornells, Antoni
Highlights: Music-based interventions integrate most of the principles of motor training and multimodal stimulation. The use of music in rehabilitation can improve motor and cognitive functions of subacute and chronic stroke patients. Music-based interventions lead to better mood and quality of life in stroke patients than conventional approaches. Future studies should better address methodological aspects to improve the level of evidence of these interventions. Abstract: Music-based interventions have emerged as a promising tool in stroke motor rehabilitation as they integrate most of the principles of motor training and multimodal stimulation. This paper aims to review the use of music in the rehabilitation of upper extremity motor function after stroke. First, we review the evidence supporting current music-based interventions including Music-supported Therapy, Music glove, group music therapy, Rhythm- and music-based intervention, and Musical sonification. Next, we describe the mechanisms that may be responsible for the effectiveness of these interventions, focusing on motor learning aspects, how multimodal stimulation may boost motor performance, and emotional and motivational aspects related to music. Then, we discuss methodological concerns in music therapy research related to modifications of therapy protocols, evaluation of patients and study designs. Finally, we highlight clinical considerations for the implementation of music-based interventions in clinical settings.